UNIVERSITY STUDENTS’ PERCEPTION OF USING SOCIAL MEDIA FOR LEARNING ENGLISH - Meldini Sopyan Yuniar; Ine Rahayu Purnamaningsih (IKIP Siliwangi, 2022)
Nowadays, many students use social media not only to communicate and get entertainment, but also to learn. Since students often use social media to learn various things, English-related content is one of the things that often be on their search. By using the social media, students are able to find various English content that may allow them to learn new things about English.This study aims to find out students' perceptions of using social media for learning English. The participants of this study are five eight-semester university students majoring in English Education. The researchers used a qualitative descriptive method with a questionnaire as the instrument. The results show that learning English from social media is quite effective; especially useful for interacting and communicating; increasing their ability to read, write, listen, and speak; and probably best to be alternative media to learn English but not being the primary source because social media could be a distraction while studying. Keywords: Students’ Perception, Social Media, Learning English